Sequenced Place and Goal components express Source of motion: a cross-linguistic study - Robbers, Maja (Linguistik Online, 2026)
This explorative study discusses a hitherto underdescribed Source of motion expression type that is based on sequencing a Place-denoting component with a Goal-denoting component. Nine languages that show this bipartite coding strategy are discussed in detail, and are compared with regard to eventhood criteria, such as shared TAM marking. This type of Source expression shows that some languages make do without dedicated Source verbs and without grammatical Source marking. Instead, they are headed by Goal verbs which are iconically ordered with Place-denoting forms. Together, they express two subevents (staying at X, going to Y), the combination of which results in a Source of motion event (leaving [from] X). The bipartite and iconically ordered Source expression type is a crosslinguistically attested strategy which shows some formal variety across languages. The bipartite strategy is further contrasted with Goal/ Source expressions where Path is inferred from lexical semantic contrast.